Load balancing strategies in software defined networks - Shrivastava, Gourav; Kaushik, Praveen; K.Pateriya, R. (International Journal of Engineering and Technology, 2018)
In the past few years, network requirements have been changing frequently as the amount of data traffic increasing exponentially so it is difficult to utilize the full capacity of network resources. Software Defined Networking (SDN) is emerging as a new networking technology which decouples the control plane from the data plane in the network devices. Separation of control and data plane allows a network administrator a better control over network management and also enables new development through network programmability. Presently Open-Flow is the most popular SDN protocol which provides communication between network devices and controller. In this paper, the Round Robin algorithm is compared with the Dynamic load balancing algorithm using the OpenFlow protocol in SDN under varying load conditions of TCP and UDP traffic. Experimental analysis shows that the dynamic load balancing strategy works better than the Round Robin load balancing.Â Â